Hypocalcemia Induced by Raloxifene - D.T. Vu, Thuy; Varadarajan, Suresh; Seeman, Ego; Jerums, George; J. MacIsaac, Richard (Current Drug Safety, 2012)
Raloxifene is an anti-resorptive agent used in postmenopausal osteoporosis. This is the first report of the occurrence of clinically significant hypocalcemia following raloxifene treatment in a patient with occult vitamin D deficiency. Since vitamin D deficiency is widely prevalent in the community, screening for vitamin D deficiency and its correction is advisable before the initiation of anti-resorptive therapy.
Keywords: vitamin D deficiency